An Escherichia coli-Based Assay to Assess the Function of Recombinant Human Hemichannels. (February 2017) - Krishnan, Srinivasan; Fiori, Mariana C.; Whisenant, Ty E.; Cortes, D. Marien; Altenberg, Guillermo A.; Cuello, Luis G.
Connexins form the gap junctional channels that mediate cell-to-cell communication, and also form hemichannels present at the plasma membrane. Hemichannels are permeable to small hydrophilic compounds, including molecules involved in autocrine and paracrine signaling. An abnormal hemichannel opening causes or contributes to cell damage in common human disorders (e.g., cardiac infarct, cerebrovascular accidents, deafness, skin diseases, and cataracts) and is therefore a potential pharmacological target. The discovery of useful hemichannels inhibitors has been hampered in part by the lack of suitable high-throughput functional assays. Here, we developed and characterized an assay useful to assess the function of hemichannels formed by human connexins expressed in a genetically modified Escherichia coli strain. The LB2003 cells, devoid of three key K + uptake transport mechanisms, cannot grow in low-[K + ] medium, but expression of Cx26, Cx43, or Cx46 rescues their growth defect (growth complementation). We developed a protocol for a simple, inexpensive, easily scalable, reproducible, and sensitive assay that should be useful for the discovery of new and better hemichannel inhibitors based on the analysis of small-compound libraries.